Saree on Fireside: Fatal Burn in an Elderly Nepalese Female - Atreya, A.; Bashyal, G.; Gyawali, L.; Acharya, J.; Nepal, S. (Kathmandu University Medical Journal, 2022)
As winter approaches, people in the land of rural Himalayas commonly use fire as the source of heat. Many accidents occur in the process, and mostly the victims are among unattended children and the elderlies. We present a case from rural Nepal where an elderly female sustained fatal burn injuries. Advanced age, greater surface area, and secondary infection were the complicating factors. In the present case, the victim’s clad cloth (Saree) was the harbinger to death. Prevention of infection following burn and control of sepsis still remains the mainstay of treatment in burn victims.